A Characterization of Strategy-Proof Social Choice Functions for Economies with Pure Public Goods - Salvador Barbera; Matthew Jackson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
We characterize strategy-proof social choice functions when individual have strictly quasi-concave, continuous and satiated utility functions on convex subsets |R^l, representing preferences for the provision of l pure public goods. When specialized to the case l=1, these assumptions amount to requiring that preferences are single peaked, and for such a domain there exists a wide class of strategy-proof social choice functions. These were studied by Moulin (1980) under additional assumptions. Our first results characterize the complete class, after an appropriate extension of the single-peakedness condition. The new characterization retains the flavor of Moulin's elegant representation theorem. For the general l-dimensional case, previous results have shown that there is no efficient, strategy-proof, nondictatorial social choice function, even within the domain restrictions under consideration [Border and Jordan (1983), Zhou (1991)]. In fact, Zhou's powerful results indicates that nondictatorial strategy-proof s.c.f.'s will have a range of dimension one. This allows us to conclude with a complete characterization of all strategy-proof s.c.f.'s on |R^l, because restrictions of preferences from our admissible class to one dimensional subsets satisfy the slightly generalized notion of single-peakedness that is used in our characterization for the case l=1. We feel that a complete knowledge of the class of strategy-proof mechanisms, in this as well as in other contexts, is an important step in the analysis of the trade-offs between strategy-proofness and other performance criteria, like efficiency.
Keywords: 330